A Specific Predicting Model for Screening Skip Metastasis From Patients With Negative Central Lymph Nodes Metastasis in Papillary Thyroid Cancer - Yang, Zheyu; Heng, Yu; Zhao, Qiwu; Cao, Zichao; Tao, Lei; Qiu, Weihua; Cai, Wei (Frontiers in Endocrinology, 2021)
Skip metastasis is a specific type of papillary thyroid cancer lymph node metastasis (LNM). The present study aimed to clarify the typical clinical characteristics of skip metastasis and optimize the prediction model, so as to provide a more individual treatment mode for skip metastasis. We retrospectively analyzed 1075 PTC patients with different status of lymph node metastasis from two clinical centers. Comparisons have been made between patients with skip metastasis and others types of LNM. Univariate and multivariate analyses were performed to detect the risk factors for skip metastasis with negative LNM, and a nomogram for predicting skip metastasis was established. The rate of skip metastasis was 3.4% (37/1075). Comparing with other types of LNM, significant differences showed in tumor size, upper portion location, thyroid capsular invasion, and ipsilateral nodular goiter with central lymph node metastasis (CLNM) Group, and in age and gender with lateral lymph node metastasis (LLNM) Group. Four variables were found to be significantly associated with skip metastasis and were used to construct the model: thyroid capsular invasion, multifocality, tumor size > 1 cm, and upper portion. The nomogram had good discrimination with a concordance index of 0.886 (95% confidence interval [CI], 0.823 to 0.948). In conclusion, the significant differences between skip metastasis and other types of LNM indicated that the lymph node drainage pathway of skip metastasis is different from either CLNM or LLNM. Furthermore, we established a nomogram for predicting risk of skip metastasis, which was able to effectively predict the potential risk of skip metastasis in patients without preoperative LNM clue.